1977
DOI: 10.1071/bi9770527
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Segments of Rabbit a-Tropomyosin

Abstract: Rabbit IX-tropomyosin was cleaved into two pieces at the cysteine residue of each chain. The products were separated by chromatography and characterized by amino acid analysis, molecular weight determination in benign and denaturing solvents, optical rotation and circular dichroism. When the cleavage reaction was carried out under mild conditions which preserve the two-chain structure there was considerable loss of IX-helix in each segment.Thermal stability studies, monitored by optical rotation and circular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…Fluorescence probe studies with the label at Cys 190 have indicated that the probe responds to the unfolding in the pretransition temperature region (12, 13, 33). The main transition at 47°C is due to unfolding of the C-terminal region and the transition at about 54°C is due to unfolding in the N-terminal region (25, 26, 32). The relative areas under the derivative curves in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence probe studies with the label at Cys 190 have indicated that the probe responds to the unfolding in the pretransition temperature region (12, 13, 33). The main transition at 47°C is due to unfolding of the C-terminal region and the transition at about 54°C is due to unfolding in the N-terminal region (25, 26, 32). The relative areas under the derivative curves in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The length of coiled-coil regions is likely to be greater in the native keratin since the potential number of residues which can take up this conformation is 103 and 100 respectively for the two types of polypeptide chains involved (Fraser et al 1976) (~94 % ex-helix and a potential length of 15 nm). Fragments of the ex-helical muscle protein, a-tropomyosin, obtained by either chemical splitting or limited proteolysis (Woods 1977;Pato et al 1981) all show a lower ex-helix content than the parent protein. The molecular weight of 50200 for the helix-rich particle excludes the similar three subunit structure 'of Crewther and Dowling (1971), Crewther (1976) in favour of a four-chain particle.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…The molecule unfolds, with increasing temperature or concentration of denaturant, in two distinct stages (Woods, 1969;Pont & Woods, 1971;Satoh & Mihashi, 1972). The first stage, the pretransition, appears to involve unfolding of the C-terminal half of the molecule, and the second stage, the main transition, involves the complete unfolding of the molecule (Chao & Holtzer, 1975;Woods, 1977;Betcher-Lange & Lehrer, 1978;Lehrer, 1978;Pato & Smillie, 1978;Potekhin & Privalov, 1978). Woods (1976) has described this as an equilibrium between the native molecule, N, a partially unfolded (in the C-terminal half) intermediate state, X, and the completely denatured tropomyosin, D; Le., N F= X D. Studies of the fluorescence of probes attached to cysteine-190 (Graceffa & Lehrer, 1980;Betteridge & Lehrer, 1983), of the N M R of histidine-153 (Edwards & Sykes, 1980), and of differential scanning calorimetry of tropomyosin (Williams & Swenson, 1981;Potekhin & Privalov, 1982) have provided more direct evidence for multistate thermal equilibria.…”
Section: Dynamic Equilibrium Between the Two Conformational States Ofmentioning
confidence: 99%